PENGARUH DISIPLIN KERJA, STRES KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MALANG - Ainun Rahmatulloh; Hadi Sunaryo; A. Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of this research is to describe work discipline, work stress, work motivation and employee performance and to know the influence of work discipline, job stress, and work motivation on partial employee performance. The method in this research is using quantitative method. This type of research is replication research.The sample of this research is employees at the Office of Population and Civil Registry of Malang Regency using systematic sampling method, which is as much as 73 respondents. Methods in collecting data using questionnaires. The method of analysis used in this research is multiple linear regression analysis with SPSS 14.0 FOR WINDOWS.The results of this study indicate that work discipline, job stress, and work motivation have a significant partial postive influence on the performance of employees of the Office of Population and Civil Registry of Malang Regency.Keywords: Work Discipline, Job Stress, Work Motivation, and Employee Performance